Between-days reliability and sensitivity of common fatigue measures in rugby players - Roe, G.; Darrall-Jones, J.; Till, K.; Phibbs, P.; Read, D.; Weakley, J.; Jones, B. (International Journal of Sports Physiology and Performance, 2016)
This study established the between-days reliability and sensitivity of a countermovement jump (CMJ), plyometric push-up, well-being questionnaire, and whole-blood creatine kinase concentration ([CK]) in elite male youth rugby union players. The study also established the between-days reliability of 1, 2, or 3 CMJs and plyometric-push-up attempts. Twenty-five players completed tests on 2 occasions separated by 5 d (of rest). Between-days typical error, coefficient of variation (CV), and smallest worthwhile change (SWC) were calculated for the well-being questionnaire, [CK], and CMJ and plyometric-push-up metrics (peak/mean power, peak/mean force, height, flight time, and flight-time to contraction-time ratio) for 1 maximal effort or taking the highest score from 2 or 3 maximal efforts. The results suggest that CMJ mean power (2 or 3 attempts), peak force, or mean force and plyometric-push-up mean force (from 2 or 3 attempts) should be used for assessing lower- and upper-body neuromuscular function, respectively, due to both their acceptable reliability (CV < 5%) and good sensitivity (CV < SWC). The well-being questionnaire and [CK] demonstrated between-days CVs >5% (7.1% and 26.1%, respectively) and poor sensitivity (CV > SWC). The findings from this study can be used when interpreting fatigue markers to make an objective decision about a player`s readiness to train or compete.